Who am I self esteem, media and decision making - Davis, Lidija; Video Education Australasia (Bendigo, Victoria : Video Education Australasia, 1999)
This program explores how streotypes of youth and beauty are promoted, and how they influence our self esteem. Also explores the three myths, which is'thin' myth,'youth' myth and the'relationship' myth
Title from title screen
Executive producer, Neil Barrett, Robyn Holdsworth ; editor/graphics, drew Hariot ; sound, Joel de Courcy Browne, Claudone Holt ; camera, Sue Roebrts, Sasha Trikojus, Charles Jackson
Keywords: Self-esteem; Self-confidence; Decision making